Spectroscopic characterization of H2 and D2 helicon plasmas generated by a resonant antenna for neutral beam applications in fusion. (30th January 2017) - Marini, C.; Agnello, R.; Duval, B.P.; Furno, I.; Howling, A.A.; Jacquier, R.; Karpushov, A.N.; Plyushchev, G.; Verhaegh, K.; Guittienne, Ph.; Fantz, U.; Wünderlich, D.; et al.
Abstract: A new generation of neutral beam systems will be required in future fusion reactors, such as DEMO, able to deliver high power (up to 50 MW) with high (800 keV or higher) neutral energy. Only negative ion beams may be able to attain this performance, which has encouraged a strong research focus on negative ion production from both surface and volumetric plasma sources. A novel helicon plasma source, based on the resonant birdcage network antenna configuration, is currently under study at the Swiss Plasma Centre before installation on the Cybele negative ion source at the Institute for Magnetic Fusion Research, CEA, Cadarache, France. This source is driven by up to 10 kW at 13.56 MHz, and is being tested on a linear resonant antenna ion device. Passive spectroscopic measurements of the first three Balmer lines α, β and γ and of the Fulcher- α bands were performed with an f /2 spectrometer, for both hydrogen and deuterium. Multiple viewing lines and an absolute intensity calibration were used to determine the plasma radiance profile, with a spatial resolution <3 mm. A minimum Fisher regularization algorithm was applied to obtain the absolute emissivity profile for each emission line for cylindrical symmetry, which was experimentally confirmed. An uncertainty estimate of the inverted profiles was performed using a Monte Carlo approach. Finally, a radiofrequency-compensated Langmuir probe was inserted to measured the electron temperature and density profiles. The absolute line emissivities are interpreted using the collisional–radiative code YACORA which estimates the degree of dissociation and the distribution of the atomic and molecular species, including the negative ion density. This paper reports the results of a power scan up to 5 kW in conditions satisfying Cybele requirements for the plasma source, namely a low neutral pressure, p ⩽ 0.3 Pa and magnetic field B ⩽ 150 G.